ORIENTALIST APPROACHES TO THE QUR’AN: Epistemic Motifs, Power Relations, and Contemporary Muslim Responses - Munawir, Munawir; Safei, Abdullah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Orientalist scholarship on the Qur’an has significantly shaped global academic and socio-religious discourse through its epistemic assumptions, theological frameworks, and comparative methodologies. This article investigates dominant epistemic motives underlying orientalist approaches to the Qur’an and analyzes how such motives operate within broader knowledge–power relations. Employing qualitative library research and content analysis within a sociology of knowledge framework, this study examines key orientalist works and maps their recurring argumentative structures. The findings reveal three central epistemic tendencies: (1) delegitimizing the Qur’an as divine revelation, (2) constructing negative assessments of the Prophet Muhammad, and (3) positioning the Qur’an as a derivative text of Jewish–Christian traditions. These discursive tendencies are embedded within Western theological, historical, and colonial contexts that privilege Judeo-Christian epistemic norms as benchmarks for evaluating Islamic revelation. The article further highlights contemporary Muslim scholarly responses—particularly within the Asia–Pacific region—that challenge orientalist paradigms through postcolonial critique, interdisciplinary hermeneutics, and socio-religious renewal in Islamic higher education. This study contributes to ongoing debates on religion and society by framing orientalist Qur’anic studies not merely as textual critique, but as socio-epistemic discourse with implications for Muslim identity, scholarship, and interreligious relations in the Asia–Pacific context.